A novel method to categorize stretch-shortening cycle performance across maturity in youth soccer players - Pedley, J. S.; Lloyd, R. S.; Read, P. J.; Moore, I. S.; Myer, G. D.; Oliver, J. L. (The Journal of Strength and Conditioning Research, 2022)
This study used a novel method to categorize stretch-shortening cycle (SSC) function during a drop jump (DJ) using the force-time curve. This method was then used to determine the effect of maturity status upon SSC function and effect of SSC function on DJ performance. Prepeak, circa-peak, and postpeak height velocity male youth soccer players completed a preseason 30-cm DJ onto a force plate. Stretch-shortening cycle function was categorized as poor (impact peak and not spring-like), moderate (impact peak and spring-like), or good (no impact peak and spring-like). Interactions between SSC function and maturity status, and SSC function and kinetic variables were explored. Youth soccer players displaying good SSC function were older and more mature than those with poor SSC function; however, 9.9% of post peak height velocity still displayed poor SSC function. Players with good SSC function recorded significantly shorter ground contact times, reduced time between peak landing and takeoff force, reduced center of mass displacement, and significantly greater takeoff forces than players with moderate and poor SSC function (all p < 0.05). SSC function during a standardized DJ improves with maturation, but a portion of mature players still demonstrate poor SSC function. Good SSC function was associated with improved DJ outcome measures except jump height. Tailored training interventions based on SSC competency may be required to optimally enhance SSC function.